Bio-sourced flexible supramolecular glasses for dynamic and full-color phosphorescence - Fei Nie; Dongpeng Yan (Nature Communications)
Abstract Glass, a diverse family of amorphous materials, has significantly advanced human society across various fields. The demand for flexible ultrathin glass, driven by modern optical displays and portable optoelectronics, presents challenges in energy consumption, fabrication complexity, and recycling. Here, we demonstrate flexibility and full-color luminescence in large-scale ultrathin glasses derived from readily available natural resources, specifically egg albumen (EA) and gelatin (GEL), via an evaporation-driven self-assembly process. The dynamic crosslinked networks formed through hydrogen bonding between EA and GEL impart both high hardness and flexibility to the glasses, with hardness and flexural strength values comparable to state-of-the-art inorganic and organic glasses. Additionally, the EA–GEL-based glasses exhibit excitation-dependent and time-gated chiral ultralong phosphorescence with color from blue and red, and a lifetime of up to 180.4 ms. With their easy processability and full-color emission, these biogenic glasses can be fabricated into anti-counterfeiting patterns and optical information codes.